The Generic Uniqueness of Yuri Klavdiev’s Play „The Victorious One” - Safargaleeva, Evgeniia (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article discusses the work of one of the most outstanding and original representatives of the “New Drama”, the playwright Yuri Klavdiev (born in 1974). At the most recent stage of his creative work, the author shows interest in canonical genres, in particular, he refers to the medieval genre of the “miracle play”. His drama Pobedonosets [The Victorious One] (2015) is based on the artistic principles and poetics of the genre. The article analyzes the play taking into account the characteristics of the miracle, indicating the influence of the genre on the structure and main idea of the play, as well as on the perception of the work by the reader/viewer.